Actitudes hacia la conservación ambiental en estudiantes de la facultad de ingeniería química de la Universidad Nacional de la Amazonía Peruana. Iquitos. - Guimet Soto, Herman Raul (2018)
ABSTRACT Descriptive non-experimental study, has as goal, to find the differences in attitudes toward environmental conservation among students of the Faculty of Chemical Engineering from the National University of the Eastern Peruvian in Iquitos - 2011; according to the level of university education, sex, age and place of residence; the population consisted of 189 students and is working with a sample of 111 students; the technique used for data collection was the survey and design and valid as an instrument the Likert-type scale; the results showed that the students of the II level, presented the best attitudes, followed by the III, IV, I, and last place is the V level; well same attitudinal differences were found between the students of the four district, such as place of residence; with regard to gender differences are shown in favor of the male sex and with respect to the variable chronological age can say that the attitudes of the older students, they occupy the first place, followed by the younger and ending with the students of the intermediate group. The variable level of university education, does not seem to have a distinctive role in attitudes toward environmental conservation. In spite of the fact that the official curriculum structure includes the environmental area. All this leads to the need to strengthen the curriculum structure that includes the environmental area.